Designing a Virtual Lan Network Using Manageable Switches at Smkn 3 Bengkulu City - Dwinata, Renaldo; Kalsum, Toibah Umi; Alamsyah, Hendri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to design a VLAN network using a manageable switch at SMKN 3 Kota Bengkulu. The research method used in this study is the PPDIOO method. The hardware used in the configuration of the Virtual LAN network design is a Mikrotik Haplite Rb941 4 port and a D-link manageable switch, while the software used for the configuration is the Windows 10 operating system and a web browser. Data collection was carried out by observation, laboratory studies, and literature studies. The results showed that the quality of the VLAN network was better than the actual network as measured by the parameters of throughput, packet loss, delay, and jitter. The throughput value on the actual network was 198 Kb (poor) and increased on the VLAN network by 1367 kb (good). The actual network delay value was 3.56 ms (moderate) and decreased on the VLAN network by 2.53 ms (good). The jitter value also decreased from 8.30 ms (moderate) to 7.45 ms (good). Meanwhile, the packet loss value on the actual network and VLAN are both 0% (very good). In addition, the performance of file transfer speed between PCs using VLAN networks is better than the actual network, which is 10.9 MB/s for the actual network and 11 MB/s for the VLAN network. The use of VLAN networks can also improve network security because it can separate teacher and administration PCs as evidenced by the two PCs not being connected when the ping test was carried out.